GE_GERICHTE A/771/2022 vom 2. September 2022 - GE Cour de justice (2022)
RETRAIT DE PERMIS;FAUTE GRAVE;SIGNALISATION ROUTIÈRE;PRIORITÉ(CIRCULATION) | LCR.16.al2; LCR.16c.al1.leta; LCR.27.al1; OSR.36.al1; LCR.90.al1; LCR.16.al3; LCR.16c.al2.leta